Augmented Reality-based Discovery Learning: an Effective Strategy to Improve Critical Thinking in Sciences for Grade IV - Wahyu Utami, Annisa Nurrahma; Rusnilawati, Rusnilawati (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2025)
This study examines the effectiveness of the Discovery Learning model supported by Augmented Reality (AR) media in enhancing critical thinking skills among Grade IV students at SDN 02 Kuto on the topic of plants as a source of life. It also explores how this method compares to the Problem-Based Learning model using PowerPoint media. The research aimed to determine whether Discovery Learning with AR can improve students’ critical thinking skills and engagement. The study also seeks to identify differences in critical thinking outcomes between the experimental and control groups. A quantitative approach was applied with a quasi-experimental design. The study involved 40 students, divided into an experimental group (20 students) using Discovery Learning with AR and a control group (20 students) using Problem-Based Learning with PowerPoint. Data collection utilized validated and reliable multiple-choice and essay tests, analyzed through N-Gain and independent t-tests. The findings showed a significant improvement in critical thinking skills in the experimental group compared to the control group. The N-Gain analysis indicated 66% effectiveness in the experimental group, categorized as moderately effective. The independent t-test revealed a significant difference in critical thinking aspects between the two groups. This study concludes that the Discovery Learning model supported by AR media effectively fosters critical thinking skills and engagement in learning. By integrating innovative teaching strategies with digital technologies, this approach addresses the challenges of 21st-century education and creates an interactive and enjoyable learning environment.